Building and developing a team of Vietnamese youth according to Ho Chi Minh's will - Dr. Mai Quoc Dung, Mai Quoc Dung; Nhung, Hoang Thi; Trang, Hoang Thi (Future Science / FSH-PH Publications, 2022)
In Ho Chi Minh's thought, the issue of caring, fostering and educating the young generation holds an extremely important position. Because youth is the backbone of the nation, the future of the nation. In his Will, Ho Chi Minh once again admonished: